Non-canonical Wnt signalling regulates scarring in biliary disease via the planar cell polarity receptors - Wilson,DH; Jarman,EJ; Mellin,RP; Wilson,ML; Waddell,SH; Tsokkou,P; Younger,NT; Raven,A; Bhalla,SR; Noll,ATR; Damink,SWO; Schaap,FG; et al. (Nature Communications, 2020)
The number of patients diagnosed with chronic bile duct disease is increasing and in most cases these diseases result in chronic ductular scarring, necessitating liver transplantation. The formation of ductular scaring affects liver function; however, scar-generating portal fibroblasts also provide important instructive signals to promote the proliferation and differentiation of biliary epithelial cells. Therefore, understanding whether we can reduce scar formation while maintaining a pro-regenerative microenvironment will be essential in developing treatments for biliary disease. Here, we describe how regenerating biliary epithelial cells express Wnt-Planar Cell Polarity signalling components following bile duct injury and promote the formation of ductular scars by upregulating pro-fibrogenic cytokines and positively regulating collagen-deposition. Inhibiting the production of Wnt-ligands reduces the amount of scar formed around the bile duct, without reducing the development of the pro-regenerative microenvironment required for ductular regeneration, demonstrating that scarring and regeneration can be uncoupled in adult biliary disease and regeneration.